2007
DOI: 10.1021/bi701275p
|View full text |Cite
|
Sign up to set email alerts
|

Helical α-Synuclein Forms Highly Conductive Ion Channels

Abstract: Alpha-synuclein (alphaS) is a cytosolic protein involved in the etiology of Parkinson's disease (PD). Disordered in an aqueous environment, alphaS develops a highly helical conformation when bound to membranes having a negatively charged surface and a large curvature. It exhibits a membrane-permeabilizing activity that has been attributed to oligomeric protofibrillar forms. In this study, monomeric wild-type alphaS and two mutants associated with familial PD, E46K and A53T, formed ion channels with well-define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
140
1
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(159 citation statements)
references
References 55 publications
13
140
1
5
Order By: Relevance
“…It was reported that at concentrations of 140 -700 nM, ␣-syn could form pores in the planar membranes, but only in the presence of the negatively charged or nonlamellar lipids (49). In our control experiments without VDAC, a pore formation activity of ␣-syn has never been observed in neutral diphytanoyl-phosphatidylcholine membranes used in our experiments and at ␣-syn concentrations up to 300 nM.…”
Section: ␣-Syn Reversibly Blocks Vdac Reconstituted In Planar Lipidmentioning
confidence: 38%
“…It was reported that at concentrations of 140 -700 nM, ␣-syn could form pores in the planar membranes, but only in the presence of the negatively charged or nonlamellar lipids (49). In our control experiments without VDAC, a pore formation activity of ␣-syn has never been observed in neutral diphytanoyl-phosphatidylcholine membranes used in our experiments and at ␣-syn concentrations up to 300 nM.…”
Section: ␣-Syn Reversibly Blocks Vdac Reconstituted In Planar Lipidmentioning
confidence: 38%
“…The ␣-synuclein-mediated increase in DATmediated inward currents can be a consequence of the direct interactions between these two proteins or secondary to formation of conductive pores (67), a result of pathological levels of ␣-synuclein inside the neuron. These membrane pores can influence membrane conductance (35,68), which in turn can impact DAT properties. The data presented in this study cannot exclude these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of ␣-Syn to membranes might induce the permeabilization of lipid bilayers via pore or conductive ion channel formation (22)(23)(24)(25). Alternatively, ␣-Syn has been suggested to induce membrane remodeling events, such as the nascent budding and tubulation of vesicles (26 -28).…”
Section: ␣-Synuclein (␣-Syn)mentioning
confidence: 99%